Estado, educación y pobreza: Nuevas vinculaciones a partir de las políticas públicas focalizadas - Godino Morales, Carmen B. (2022)
This paper deals with the so called public focused policies which arose in our country as an answer to the high social cost produced by the application of neoliberal policies.One of the axis that croseis the paper is the concept of poverty, as it will be shown that most of the public policies justify their existence on trying to solve it.